Study Habits and Study Skills of Nursing Licensure Examination Takers from 2015 to 2019 - Cyralehn R. Baligod; Lorie Mae S. Balas; Robie-Rose D. Bambasi; Xyla Faith A. Ancheta; Yolanda H. Abedoza; Lovelites D. Zamora; Angelito E. Alvarado (Humanistic Network for Science and Technology (HNST), 2021)
Study habits and study skills of nursing licensure examination takers from 2015-2019 of the educational institution. The study aims to identify the study habits, and study skills carried out by board takers, ascertain the relationship between study habits and skills and determine the significant difference of study skills and study habits in nurse licensure examination. An online survey was done due to limited interactions brought by the pandemic. The respondents of the study are takers of nursing licensure examination from 2015 to 2019 who graduated at educational institution. Total population sampling technique is used, the study has a total of 97 respondents but due to the rising Covid 19 cases only 45 respondents are met. The study employed a descriptive correlational approach and quantitative research design to measure the relationships of study habits and study skills for nursing licensure examination. A Pearson correlation revealed that study skills and study habits of the respondents does not have significant relationship between study habits and study skills to nursing licensure examination. Hence, the study skills and study habits alone of the respondents does not ensure passing the Nursing Licensure Examination. Implications of the study in organization and the directions for the future research are also provided.Keywords: nursing licensure examination; examination result; study skills; study habits